Development Of Vehicle Ignition Using Fingerprint - Jamil Alsayaydeh, Jamil Abedalrahim; Indra, Win Adiyansyah; Wong, Adam Yoon Khang; P. Jkatisan, Dhanigaletchmi; Shkarupylo, Vadym (Asian Research Publishing Network (ARPN), 2019)
This paper is about building a prototype of vehicle ignition using fingerprint sensor. This system can prevent the vehicles from being stolen. It is developed to control the ignition of the vehicle through the fingerprint scanner. This system consists of GSM SIM 900 that connects to the Arduino which is the microcontroller of the project. To make sure the system is secure, only authorized fingerprint is paired with the Arduino to start the ignition. Vehicles ignite when the enrolled fingerprint is matched against the fingerprints in the database while users with no match in the database are prevent from igniting the vehicle. A theft alarm from buzzer, a notification to the owner’s mobile phone via GSM SIM 900 and status display in the LCD are the appropriate signal to the owner. This article describes briefly in detail about the design and implementation of the ignition system